Listening to Music, Biomechanics of Gait and Sports Performance: A Narrative Review - Maryam Zare Mojtahedi; Ali Fatahi; Farhad Tabatabai Ghomsheh; Amirali Jafarnezhadgero (Physical Treatments)
Purpose: Music is one of the most widely used artistic elements in different societies. Today, it has drawn much attention due to its extensive societal effects. Music stimuli can affect human sports performance and gait as important indicators of different health conditions. This review study investigates how listening to music affects sports performance and gait. Methods: This systematic review based on a descriptive-analytical method was conducted to investigate the interaction of music with sports performance and gait. We searched in reliable citation databases based on the keywords “gait”, “music”, and “biomechanics” in articles published between 2003 and 2023. After the final screening, the full texts of 11 studies were extracted and analyzed. Results: Based on the interpretation of the qualitative findings of the articles, it was observed that music can improve sports and gait performance. For example, changes in walking speed, step length, rhythm, and step time were significantly improved in the gait kinematic section. Conclusion: Listening to music improves motor performance in clinical settings and functional environments. In addition, music can be used as a therapeutic agent or directly in treating people with movement disorders.